Distribution of the Fraunhofer Diffraction Intensity by a Rectangular Slit Using a Razor Blade - Eli Trisnowati; Putut Marwoto; Retno Sri Iswari; Edy Cahyono (Postgraduate, University of Mataram, 2022)
This research was conducted by making a rectangular slit using a razor blade as a narrow gap in the Fraunhofer diffraction experiment. The intensity distribution measurement on the resulting diffraction pattern uses a voltage divider circuit. This circuit takes advantage of the nature of the LDR, which changes resistance when exposed to light. Experiments show that a diffraction pattern screen when a 560 nm coherent light passes through a narrow rectangular slit made of razor cut. We measured the narrow gap using a tracker application with the resulting gap size (0.3564 x 0.4677) mm. The ratio of the intensity distribution of the x-axis bright pattern on the Fraunhofer diffraction by a rectangular slit with slit size height x width = (0.4677 x 0.3564) mm from b = -5p to 5p (maximum 4, maximum 3, maximum 2, maximum 1, central maximum, maximum 1, maximum 2, maximum 3, maximum 4) is 0.000873; 0.000763; 0.005395; 0.020583; 1; 0.039658; 0.008088; 0.002554; 0.001218. The ratio of the intensity distribution of the y-axis bright pattern on the Fraunhofer diffraction by a rectangular slit with slit size height x width = (0.4677 x 0.3564) mm from g = -5pÂ to 5p (maximum 4, maximum 3, maximum 2, maximum 1, central maximum, maximum 1, maximum 2, maximum 3, maximum 4) is 0.001890; 0.001469; 0.002447; 0.040516; 1; 0.037141; 0.006482; 0.001690; 0.000440. This study indicates that diffraction experiments and the measurement of the diffraction patternâ€™s intensity can be carried out with simple materials and equipment and can be used in the correct experiment.